Pengembangan SDM Berjiwa Wirausaha: Mindset, Skill, dan Aksi di Kelurahan Galang Baru, Batam - Hutri Agus Romi; Mefri Yudi Wisra; Mulyadi, Mulyadi (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
This report presents the implementation of a Field Work Lecture (KKL) program focused on enhancing entrepreneurial mindset, skills, and actions in Galang Baru Sub-district, Galang District, Batam City, Riau Islands Province. The primary issue addressed is the limited entrepreneurial orientation among the local community, particularly in utilizing available local resources. Despite the area's considerable potential to foster entrepreneurship, the prevailing challenges include a lack of entrepreneurial mindset, insufficient technical competencies, and minimal concrete efforts to initiate business ventures. The KKL program aimed to provide targeted education and training to strengthen the quality of human resources capable of engaging in entrepreneurship. Conducted over two days, from May 17 to May 18, 2025, the program involved 32 participating students. The methodological approach emphasized community engagement, prioritizing the development of three core entrepreneurial elements: mindset, skills, and practical action. The implementation process included field observation, preparation of outreach materials, community engagement, training sessions, and mentorship for locally owned businesses. The results of the program indicate a substantial improvement in community awareness of entrepreneurial thinking, with an increase from 40% to 85%. Similarly, mastery of entrepreneurial skills rose from 20% to 70%. Furthermore, 70% of participants demonstrated tangible entrepreneurial initiatives, either individually or in groups. These outcomes affirm that an integrated approach—encompassing mindset development, skill enhancement, and actionable initiatives—can effectively promote sustainable economic empowerment at the local level..